2013
DOI: 10.1590/s1676-06032013000200007
|View full text |Cite
|
Sign up to set email alerts
|

Flood-mediated use of habitat by large and midsized mammals in the Brazilian Pantanal

Abstract: DE LÁZARI, P.R., SANTOS-FILHO, M., CANALE, G.R. & GAIPEL, M.E. Flood-mediated use of habitat by large and midsized mammals in the Brazilian Pantanal. Biota Neotrop. 13(2): http://www.biotaneotropica. org.br/v13n2/en/abstract?article+bn02713022013 Abstract:The Brazilian Pantanal comprises a mosaic of forest and field environments harbouring a rich community of large and midsized mammals that are adapted to the annual hydrological cycle. Here we evaluated richness and composition of large and midsized mammals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 14 publications
(17 reference statements)
0
8
0
1
Order By: Relevance
“…, De Lázari et al. ). The top‐ranking RSF models showed that when jaguars were moving through the landscape and killing prey or cattle, the models were relatively simple with consistent variables among the models.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…, De Lázari et al. ). The top‐ranking RSF models showed that when jaguars were moving through the landscape and killing prey or cattle, the models were relatively simple with consistent variables among the models.…”
Section: Discussionmentioning
confidence: 98%
“…The cordilheiras generated in the wet season provide a refuge for terrestrial mammals, which they leave for the more nutrient‐rich marshes in the dry season (De Lázari et al. ). Prior researchers have found that Pantanal jaguars were rarely away from water (Crawshaw and Quigley , Cullen et al.…”
Section: Discussionmentioning
confidence: 99%
“…The responses of biological communities to the spatial and temporal variation within ATTZs are still poorly understood. Some studies have shown that terrestrial and aquatic biological communities such as vegetation (Ikeda-Castrillon et al 2011, Catian et al 2018, vertebrate animals (Figueira et al 2011, Lázari et al 2013, Valério et al 2016, Penha et al 2017 and invertebrates (Oliveira-Júnior et al 2013) can respond differently to landscape changes caused by flood and dry cycles of the Pantanal.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimate Ungulate [107] stated that they were diurnal, which was in contrast to other authors who found that they were nocturnal animals although they were active during the day, with the least activity around noon, which had the hottest hours [114]. ey were present in dry forests, riparian forests, and marshes [115] but were also found along marshes, swamps, and streams, in moist and arid environments [108]. e red brocket deer (M. rufa) preferred the interior of forests and was mostly present in deciduous and gallery forests (46%), cerrado (5%), and beach (8%) [116].…”
Section: Red Brocket Deer (Mazama Americana)mentioning
confidence: 99%